Overlapping Groundwater Service Markets in a Palm Grove in the Algerian Sahara. (2nd November 2017) - Hamamouche, Meriem Farah; Kuper, Marcel; Hartani, Tarik; Bouarfa, Sami
Abstract: Groundwater service markets are important and dynamic institutions that provide water to a wide range of farmers in many regions. However, these institutions represent arenas of complex and often antagonistic relations, which determine which farmers gain access to water and how. This study analyses the emergence and functioning of groundwater service markets from a historical perspective to advance the understanding of the role of social power games in shaping these institutions. The study was conducted in the Sidi Okba oasis in the Algerian Sahara, where over recent decades, four (in)formal, often overlapping, groundwater service markets have emerged. These markets were shaped progressively by socio‐ethnic antagonism, state intervention and economic competition between water sellers. By continuously adjusting these institutions, the highly diverse irrigation community prevented the emergence of a monopoly in groundwater sales and maintained the balance of power between water sellers and buyers by countering possible control of groundwater access by a single socio‐ethnic or economic group. The demonstrated ability of the irrigation community to craft rules to ensure these groundwater service markets function should encourage public actors to mobilize this capacity to deal with the drop in water tables, which is one adverse outcome of the 'success' of these markets. Copyright © 2020 John Wiley & Sons, Ltd. Résumé: Les marchés de service d'eau souterraine sont des institutions importantes et dynamiques qui fournissent de l'eau à un large éventail d'agriculteurs dans de nombreuses régions du monde. Ces institutions sont historiquement construites et présentent des arènes de relations complexes et souvent antagonistes, particulièrement entre vendeurs et acheteurs d'eau. Ces relations déterminent à leur tour quels agriculteurs ont accès à l'eau souterraine, et comment. Cette étude analyse l'émergence et le fonctionnement des marchés de service d'eau souterraine d'un point de vue historique afin de mieux comprendre les enjeux sociaux dans le façonnage de ces institutions. Une étude de cas a été menée dans la palmeraie de Sidi Okba, dans le Sahara algérien, où, au cours des quatre dernières décennies, quatre marchés (in)formels de service d'eau souterraine—souvent se chevauchant—ont émergé. Ces marchés ont été façonnés progressivement par des antagonismes socio‐ethniques, des interventions étatiques et des rivalités entre vendeurs d'eau cherchant à se positionner sur ces marchés devenus lucratifs. Grâce à l'ajustement continu de ces institutions, la communauté d'irrigants dans sa diversité a empêché l'émergence d'un monopole dans les ventes d'eau souterraine, en contrecarrant le contrôle possible de l'accès à l'eau souterraine par un seul groupe socio‐ethnique ou économique. La capacité de la communauté d'irrigants à élaborer des règles pour assurer le fonctionnement de ces marchés de service d'eau souterraine, devrait encourager les acteurs publics à mobiliser cette capacité pour faire face au déclin des nappes, qui est en partie le résultat du succès de ces marchés. Copyright © 2020 John Wiley & Sons, Ltd.